Analysis of Supply Chain Performance and The Efficiency of Dairy Product Suppliers at PT XYZ, Subang Sub Province - Muhardi Ahmad Kautsar; Alim Setiawan Slamet; Heti Mulyati (Eduvest - Journal of Universal Studies, 2025)
Dairy farming in West Java plays a crucial role in rural livelihoods, yet faces declining productivity due to limited feed and infrastructure. PT XYZ, a dairy processing company in Subang, encounters internal inefficiencies and external supply inconsistencies from smallholder farmers. This study aims to (1) analyze PT XYZ’s dairy supply chain using the SCOR model, (2) determine the priority weights of supply chain performance metrics, and (3) assess the efficiency of its two major suppliers KUD Larasati and KUD Parongpong using the DEA method. Data were collected via observations, interviews, literature review, and expert judgment. Performance parameters such as planning (weight 0.397), perfection (0.662), and quality (0.378) were found most critical. Efficiency analysis revealed that neither cooperative achieved consistent 100% efficiency across semesters, with issues stemming from delivery delays, inadequate infrastructure, and fluctuating milk quality. Recommendations include optimizing logistics, implementing ERP systems, and enhancing supplier coordination. Findings emphasize the need for integrated performance measurement to boost supply chain responsiveness, reduce costs, and maintain high product quality. The study highlights the importance of strategic planning and continuous evaluation to improve competitiveness and ensure sustainable milk supply chain operations.